Transplacental transfer of maternal SARS-CoV-2 antibodies in dichorionic and monochorionic twin pregnancies - Jennifer E. Stolarczuk; Monica Sosa; Mindy Pike; Alexis Baranoff; Ava Lekander; Hye Cho; Erin A. Goecker; Alexander L. Greninger; Linda O. Eckert; Janet A. Englund; Alisa Kachikis (PLoS ONE, 2025)
Background Maternal immunization relies on active transplacental transfer of immunoglobulin G. However, very little is known about the efficacy of maternal immunization in the setting of multiple gestation. We aimed to investigate transplacental transfer of maternal antibody in pregnancies with multiple gestation including mono- and dichorionic pregnancies by evaluating anti-Spike antibody transfer at delivery. Methods We conducted a cohort study among individuals with singleton or twin pregnancies who received ≥ 2 doses of an mRNA COVID-19 vaccine before delivery. We tested paired maternal and cord blood samples for anti-Spike antibody levels via Roche Elecsys® immunoassays and used linear regression to evaluate associations between pregnancy type and anti-Spike antibody levels. We included as covariates gestational age at birth, timing of last vaccine dose, number of vaccine doses, and small for gestational age birth weight. Results Between 2021−2023, we tested paired maternal and cord samples for anti-Spike antibody from 362 singleton pregnancies and 36 twin pregnancies, of which 12 and 24 were monochorionic and dichorionic, respectively. After adjusting for covariates, maternal and cord anti-Spike antibody concentrations were significantly lower in twin pregnancies compared to singleton pregnancies (beta:-0.91, 95% Confidence Interval [CI]: −1.62,-0.19; p = 0.01. beta −1.20, 95% CI: −2.36,-0.04; p = 0.04), however there was no difference in cord:maternal antibody ratios. After adjusting for covariates, there was no difference in maternal and cord antibody concentrations between dichorionic and monochorionic pregnancies, however, cord:maternal antibody ratios remained significantly lower in monochorionic compared to dichorionic pregnancies (beta:-0.49; 95% CI: −0.86,-0.13; p = 0.01). Conclusions Twin and singleton infants have similar cord:maternal maternally derived SARS-CoV-2 antibody ratios after maternal COVID-19 vaccine although maternal and cord antibody concentrations are lower in infants from twin pregnancies and specifically antibody transfer is less efficient in monochorionic pregnancies. Further research is needed to investigate impaired transplacental IgG transfer in high-risk pregnancies.